A influência da filosofia comtiana na formação da escola do direito positivo ocidental - Franco, Ricardo César (2021)
This dissertation tends to discuss, according to philosophical research, of a historical-scientific character, about the influence of Auguste COMTE's work in the development of the theory of positive law science from the second half of the 19th century until it s consolidation in the first two decades of the century XX. To this end, classic works from the Comtean repertoire will be used to establish the contemporary state of his research, particularly the Course on Positive Philosophy, The Positivist Catechism an d Discourse on the Positive Spirit. In a related way, the study will analyze the repercussion of the referred doctrine for the formation of the theory of positive law from the perspective of the works The structure of scientific revolutions, by Thomas KUHN , with the purpose of positioning the scientific revolution resulting from the work of Auguste COMTE in favor of the construction and analysis of sciences, as an aspect and constructed of human knowledge, with special attention to the science of Law. Final ly, the state of the theory of positive law will be considered the fundamental work of Hans KELSEN, the second edition of Pure Theory of Law, whose doctrine still influences Western legal culture